A kind of microwave absorbing patch and its preparation method

By adopting low-density thermoplastic resin matrix and high conductivity carbon nanotubes and white carbon black, and using laminated calendering technology, the problem of poor thickness accuracy of existing absorbent materials in the Ka band is solved, and high thickness accuracy and lightness are prepared. A wave absorbing patch with high mass, tensile strength and excellent wave absorbing performance in the Ka band.

CN116333402BActive Publication Date: 2025-02-14BEIJING INST OF ENVIRONMENTAL FEATURES
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310330118.X
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-03-30
Publication Date
2025-02-14
Estimated Expiration
2043-03-30

AI Technical Summary

Technical Problem

The thickness accuracy of existing absorbent materials in the Ka band is poor, and cannot meet the thickness requirements of the Ka band for the absorbent materials.

Method used

A low-density thermoplastic resin matrix is ​​used to form at one time by lamination, combining carbon nanotubes with high conductivity and white carbon black to prepare wave absorbing patches with high thickness accuracy, light weight and high tensile strength.

Benefits of technology

The thickness accuracy of the wave absorbing patch is achieved (up to ±0.01mm), which is convenient for mass production, meets the high requirements of the Ka band for the thickness uniformity of the wave absorbing patch in the Ka band, and has excellent wave absorbing performance in the Ka band.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116333402B_ABST
    Figure CN116333402B_ABST
Patent Text Reader

Abstract

The present invention provides an absorbing patch and a preparation method thereof, belonging to the technical field of absorbing materials. The raw materials for preparing the absorbing patch include the following components by weight: 100 parts of thermoplastic resin, 1-1.2 parts of stearic acid, 3-5 parts of white carbon black, 6-8 parts of carbon nanotubes, 0.3-0.5 parts of coupling agent, and 1-2 parts of auxiliary agent. The absorbing patch of the present invention has high thickness precision, light weight, high tensile strength, and excellent absorbing performance in the Ka band.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of wave-absorbing materials, and in particular relates to a wave-absorbing patch and a preparation method thereof. Background Art

[0002] The Ka-band has the characteristics of short wavelength and "resonant absorption". The thickness uniformity of the absorbing material in this band has a greater impact on the absorbing performance, so higher thickness accuracy is required; however, the existing absorbing materials have the problem of poor thickness accuracy and cannot meet the thickness requirements of the Ka-band for absorbing materials; therefore, there is an urgent need to provide an absorbing material with high thickness accuracy to meet the demand for Ka-band absorbing materials. Summary of the invention

[0003] In view of one or more technical problems existing in the prior art, the present invention provides an absorbing patch and a preparation method thereof. The absorbing patch provided by the present invention has high thickness precision, light weight, high tensile strength, and excellent absorbing performance in the Ka band.

[0004] The present invention provides an absorbing patch in a first aspect. The raw materials for preparing the absorbing patch include the following composition in parts by weight: 100 parts of thermoplastic resin, 1 to 1.2 parts of stearic acid, 3 to 5 parts of white carbon black, 6 to 8 parts of carbon nanotubes, 0.3 to 0.5 parts of coupling agent, and 1 to 2 parts of auxiliary agent.

[0005] Preferably, the thermoplastic resin is obtained by mixing polyethylene, polypropylene and ethylene-vinyl acetate; preferably, the mass ratio of polyethylene, polypropylene and ethylene-vinyl acetate in the thermoplastic resin is (35-45):(35-45):(15-25), preferably 2:2:1.

[0006] Preferably, the coupling agent is a silane coupling agent; preferably, the coupling agent is one or more of Si69, Si75, KH550; and / or

[0007] The auxiliary agent is one or more of an antioxidant, an antibacterial agent, and an antioxidant;

[0008] Preferably, the thickness of the absorbing patch is 0.33-0.35 mm, and the thickness accuracy is ≤±0.01 mm;

[0009] Preferably, the surface density of the absorbing patch is ≤350g / m 2 ; and / or

[0010] The tensile strength of the absorbing patch is ≥6MPa.

[0011] In a second aspect, the present invention provides a method for preparing the absorbing patch according to the first aspect, the preparation method comprising the following steps:

[0012] S1. The mixture of thermoplastic resin, stearic acid, carbon nanotubes and coupling agent is firstly refined to obtain a masterbatch;

[0013] S2. The mixture of the masterbatch, additives, carbon nanotubes, coupling agent and white carbon black is mixed to obtain a mixed material;

[0014] S3. The refining material is subjected to a second refining to obtain a refining material;

[0015] S4. rolling and rolling the smelted material to obtain the absorbing patch.

[0016] Preferably, the temperature of the first refining is 90-100° C. and the time is 30-35 min.

[0017] Preferably, the banburying temperature is 120-130° C. and the time is 20-25 min.

[0018] Preferably, the second refining is carried out at a temperature of 100 to 110° C. and for a time of 6 to 10 minutes.

[0019] Preferably, the calendering is performed using a four-roll calender; the four-roll calender comprises a first roller, a second roller, a third roller and a fourth roller arranged in sequence from front to back;

[0020] Preferably, the roller temperature of the first roller is 100-110°C; the roller temperature of the second roller is 100-110°C; the roller temperature of the third roller is 100-110°C; the roller temperature of the fourth roller is 80-85°C;

[0021] Preferably, the gap between the first roller and the second roller is 0.4-0.5 mm; the gap between the second roller and the third roller is 0.31-0.35 mm; and the gap between the third roller and the fourth roller is 0.28-0.30 mm.

[0022] Preferably, the sheet output speed of the calendering is 1.3-1.4 m / min.

[0023] Compared with the prior art, the present invention has at least the following beneficial effects:

[0024] The present invention adopts a low-density thermoplastic resin matrix and is formed in one step by layer calendering. Compared with the use of a thermosetting resin matrix, it avoids the risk of difficult-to-control thickness caused by secondary molding such as rubber vulcanization and thermosetting film curing. It has high thickness accuracy (up to ±0.01mm), is convenient for mass production, and can meet the high requirements of the Ka band for the thickness uniformity of the absorbing patch.

[0025] The low-density thermoplastic resin matrix of the present invention uses carbon nanotubes with high conductivity as absorbers, and the purpose of lightness is achieved by reducing the filling amount of the absorbers; by introducing white carbon black, the electromagnetic parameters are adjusted and reinforcement is achieved, and the absorbing patch with high thickness accuracy, light weight, high tensile strength and excellent absorbing performance in the Ka band is obtained. BRIEF DESCRIPTION OF THE DRAWINGS

[0026] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0027] Figure 1 This is a physical picture of the absorbing patch provided by the present invention;

[0028] Figure 2 is a flow chart of the preparation of the absorbing patch provided by the present invention;

[0029] Figure 3 is a reflectivity curve of the absorbing patch provided in Example 1 of the present invention;

[0030] Figure 4 is a reflectivity curve of the absorbing patch provided in Example 2 of the present invention;

[0031] Figure 5 is a reflectivity curve of the absorbing patch provided in Example 3 of the present invention;

[0032] Figure 6 It is a physical picture of the four-roll calender adopted by the present invention. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solutions and advantages of the embodiments of the present invention clearer, the technical solutions in the embodiments of the present invention will be clearly and completely described below. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0034] The present invention provides an absorbing patch in a first aspect. The raw materials for preparing the absorbing patch include the following composition in parts by weight: 100 parts of thermoplastic resin, 1 to 1.2 parts of stearic acid, 3 to 5 parts of white carbon black, 6 to 8 parts of carbon nanotubes, 0.3 to 0.5 parts of coupling agent, and 1 to 2 parts of auxiliary agent.

[0035] The present invention adopts a low-density thermoplastic resin matrix and is formed in one step by layer calendering. Compared with the use of a thermosetting resin matrix, it avoids the risk of difficult-to-control thickness caused by secondary molding such as rubber vulcanization and thermosetting film curing. It has high thickness accuracy (up to ±0.01mm), is convenient for mass production, and can meet the high requirements of the Ka band for the thickness uniformity of the absorbing patch.

[0036] The low-density thermoplastic resin matrix of the present invention uses carbon nanotubes with high conductivity as absorbers, and the purpose of lightness is achieved by reducing the filling amount of the absorbers; by introducing white carbon black, the electromagnetic parameters are adjusted and reinforcement is achieved, and the absorbing patch with high thickness accuracy, light weight, high tensile strength and excellent absorbing performance in the Ka band is obtained.

[0037] According to some preferred embodiments, the thermoplastic resin is obtained by mixing polyethylene, polypropylene and ethylene-vinyl acetate; preferably, the mass ratio of polyethylene, polypropylene and ethylene-vinyl acetate in the thermoplastic resin is (35-45):(35-45):(15-25), preferably 2:2:1.

[0038] The invention adopts a thermoplastic resin obtained by mixing polyethylene, polypropylene and ethylene-vinyl acetate as a resin matrix, and can be molded to obtain an absorbing patch with high thickness accuracy, light weight, high tensile strength and excellent absorbing performance in the Ka band.

[0039] According to some preferred embodiments, the coupling agent is a silane coupling agent; preferably, the coupling agent is one or more of Si69, Si75, KH550; and / or

[0040] The auxiliary agent is one or more of an antioxidant, an antibacterial agent, and an antioxidant.

[0041] The types of the silane coupling agent and the auxiliary agent of the present invention are not limited to the above ranges, and other silane coupling agents and auxiliary agents are also acceptable. The specific types can be adjusted according to the actual usage scenario.

[0042] According to some preferred embodiments, the thickness of the absorbing patch is 0.33-0.35 mm (for example, 0.33 mm, 0.34 mm or 0.35 mm), and the thickness accuracy is ≤±0.01 mm; preferably, the surface density of the absorbing patch is ≤350 g / m 2 ; and / or

[0043] The tensile strength of the absorbing patch is ≥6MPa.

[0044] The absorbing patch prepared by the present invention has a small thickness (only 0.33-0.35 mm), a light weight (surface density ≤ 350 g / m 2), high tensile strength (≥6MPa), absorption value in Ka band ≤-7dB, peak absorption value ≤-30dB, and excellent wave absorbing performance in Ka band.

[0045] In a second aspect, the present invention provides a method for preparing the absorbing patch according to the first aspect, the preparation method comprising the following steps:

[0046] S1. The mixture of thermoplastic resin, stearic acid, carbon nanotubes and coupling agent is firstly refined to obtain a masterbatch;

[0047] S2. The mixture of the masterbatch, additives, carbon nanotubes, coupling agent and white carbon black is mixed to obtain a mixed material;

[0048] S3. The refining material is subjected to a second refining to obtain a refining material;

[0049] S4. rolling and rolling the smelted material to obtain the absorbing patch.

[0050] It should be noted that the sum of the carbon nanotubes in steps S1 and S2 is the amount of carbon nanotubes in the composition; the total amount of coupling agents in steps S1 and S2 is the amount of coupling agents in the composition. The carbon nanotubes and coupling agents of the present invention are divided into two parts and added in multiple times, which can effectively improve the dispersibility of the carbon nanotubes; the present invention improves the uniformity of dispersion of the absorbent in the thermoplastic resin matrix by mixing the first open refining, the banbury refining, and the second open refining, and then forms the absorbing patch in one time by calendering, thereby improving the stability of the absorbing patch and the accuracy of the thickness, and realizing mass production.

[0051] According to some preferred embodiments, the temperature of the first refining is 90-100°C (for example, 90°C, 92°C, 94°C, 95°C, 96°C, 98°C or 100°C), and the time is 30-35 min (for example, 30 min, 31 min, 32 min, 33 min, 34 min or 35 min).

[0052] According to some preferred embodiments, the banburying temperature is 120-130°C (for example, 120°C, 122°C, 124°C, 125°C, 126°C, 128°C or 130°C), and the time is 20-25 min (for example, 20 min, 21 min, 22 min, 23 min, 24 min or 25 min).

[0053] According to some preferred embodiments, the temperature of the second refining is 100-110°C (for example, 100°C, 102°C, 104°C, 105°C, 106°C, 108°C or 110°C), and the time is 6-10 min (for example, 6 min, 7 min, 8 min, 9 min or 10 min).

[0054] According to some preferred embodiments, the calendering is performed using a four-roll calender; the four-roll calender comprises a first roller, a second roller, a third roller and a fourth roller arranged in sequence from front to back;

[0055] Preferably, the roller temperature of the first roller is 100-110°C (for example, 100°C, 102°C, 104°C, 105°C, 106°C, 108°C or 110°C); the roller temperature of the second roller is 100-110°C; the roller temperature of the third roller is 100-110°C (for example, 100°C, 102°C, 104°C, 105°C, 106°C, 108°C or 110°C); the roller temperature of the fourth roller is 80-85°C (for example, , which can be 80°C, 81°C, 82°C, 83°C, 84°C or 85°C); the present invention controls the roller temperature within the above range to ensure that an excellent performance absorbing patch is formed; if the roller temperature is high during the calendering process, the open-mixed material is difficult to be peeled off from the fourth roller of the calender after calendering, and the absorbing patch cannot be formed; since the roller temperature is low during the calendering process, the open-mixed material is difficult to be coated on the roller during the calendering process, and rebound and other phenomena are prone to occur, and the absorbing patch cannot be formed.

[0056] Preferably, the gap between the first roller and the second roller is 0.4-0.5 mm (for example, 0.4 mm, 0.42 mm, 0.44 mm, 0.46 mm, 0.48 mm or 0.5 mm); the gap between the second roller and the third roller is 0.31-0.35 mm (for example, 0.31 mm, 0.32 mm, 0.33 mm, 0.34 mm or 0.35 mm); the gap between the third roller and the fourth roller is 0.28-0.30 mm (for example, 0.28 mm, 0.29 mm or 0.30 mm). The present invention controls the gap between the rollers within the above range, which can ensure that the absorbing patch with high thickness accuracy and excellent Ka-band absorbing performance is formed; if the gap between the rollers of the calender is too large or too small, the thickness accuracy and Ka-band absorbing performance of the obtained absorbing patch will be significantly deteriorated.

[0057] The calendering of the present invention is carried out by a four-roll calender, which includes a first roller, a second roller, a third roller and a fourth roller arranged in sequence from front to back; specifically, the roller temperature of the first roller is set to 100-110°C; the roller temperature of the second roller is set to 100-110°C; the roller temperature of the third roller is set to 100-110°C; the roller temperature of the fourth roller is set to 80-85°C; the gap between the first roller and the second roller is set to 0.4-0.5mm; the gap between the second roller and the third roller is set to 0.31-0.35mm; the gap between the third roller and the fourth roller is set to 0.28-0.30mm. Then, the open-mixed material is placed on the rollers of the first roller and the second roller of the calender, the calendering sheet speed is set to 1.3-1.4m / min, calendering is carried out, and winding is carried out at the end of the fourth roller to obtain the absorbing patch.

[0058] According to some preferred embodiments, the sheet-out speed of the calender is 1.3-1.4 m / min. The sheet-out speed of the calender of the present invention needs to be controlled within the above range. If the sheet-out speed is too slow, the refining material placed on the AB roller of the calender has cooled in the latter stage and is difficult to be coated on the roller, and the absorbing patch is difficult to form; if the sheet-out speed is too fast, the temperature of the absorbing patch is high when it is out, and it is easy to stick together and difficult to form.

[0059] In order to more clearly illustrate the technical solutions and advantages of the present invention, the present invention is further described below in conjunction with embodiments.

[0060] The materials and reagents in the present invention can be directly purchased on the market or synthesized by themselves, and there is no limitation on the specific models.

[0061] Example 1

[0062] 1) Weighing 100 parts of a thermoplastic resin, 1 part of stearic acid, 3 parts of white carbon black, 6 parts of carbon nanotubes, 0.3 parts of a coupling agent and 1 part of an auxiliary agent in parts by weight, and dividing the carbon nanotubes and the coupling agent into two parts of equal weight; wherein the thermoplastic resin is obtained by mixing polyethylene, polypropylene and ethylene-vinyl acetate in a mass ratio of 2:2:1;

[0063] 2) setting the temperature of the open mill to 90° C., adding a thermoplastic resin and stearic acid to the open mill in sequence, and then adding a portion of carbon nanotubes and a coupling agent in four portions, and the mixing time is 20 minutes to prepare a masterbatch;

[0064] 3) Setting the internal mixer to 120° C., placing the masterbatch in the internal mixer, adding the additive, and then adding another portion of carbon nanotubes and coupling agent in four portions, and finally adding white carbon black, and mixing for 30 minutes to obtain a mixed material;

[0065] 4) The open mill is set to 100° C. The internally mixed material is put into the open mill for 6 minutes, and the material is cross-wrapped into triangle packages and rolled three times each to obtain the open-mixed material;

[0066] 5) The roller temperatures of the first roller, the second roller and the third roller of the four-roll calender are set to 100°C, and the roller temperature of the fourth roller is set to 80°C; the roller gap between the first roller and the second roller is set to 0.4mm, the gap between the second roller and the third roller is set to 0.31mm, and the gap between the third roller and the fourth roller is set to 0.28mm; the milled material is placed on the rollers of the first roller and the second roller of the calender, the calendering speed is set to 1.3m / min, calendering is performed, and winding is performed at the end of the fourth roller to obtain the absorbing patch.

[0067] Example 2

[0068] 1) Weighing 100 parts of a thermoplastic resin, 1.1 parts of stearic acid, 4 parts of white carbon black, 7 parts of carbon nanotubes, 0.4 parts of a coupling agent and 1.5 parts of an auxiliary agent in parts by weight, and dividing the carbon nanotubes and the coupling agent into two parts of equal weight; wherein the thermoplastic resin is obtained by mixing polyethylene, polypropylene and ethylene-vinyl acetate in a mass ratio of 2:2:1;

[0069] 2) setting the temperature of the open mill to 95° C., adding a thermoplastic resin and stearic acid to the open mill in sequence, and then adding a portion of carbon nanotubes and a coupling agent in four portions, and the mixing time is 23 minutes to prepare a masterbatch;

[0070] 3) The internal mixer was set to 125° C., the masterbatch was placed in the internal mixer, the additive was added, and then the other portion of carbon nanotubes and coupling agent were added in four portions, and finally white carbon black was added, and the internal mixing time was 33 minutes to obtain the internal mixing material;

[0071] 4) The open mill is set to 105° C. The internally mixed material is put into the open mill for 8 minutes, and the material is cross-wrapped into triangle packages and rolled three times each to obtain the open-mixed material;

[0072] 5) The roller temperatures of the first roller, the second roller and the third roller of the four-roll calender are set to 105°C, and the roller temperature of the fourth roller is set to 83°C; the roller gap between the first roller and the second roller is set to 0.45mm, the gap between the second roller and the third roller is set to 0.33mm, and the gap between the third roller and the fourth roller is set to 0.29mm; the milled material is placed on the rollers of the first roller and the second roller of the calender, the calendering speed is set to 1.35m / min, calendering is performed, and winding is performed at the end of the fourth roller to obtain the absorbing patch.

[0073] Example 3

[0074] 1) Weighing 100 parts of a thermoplastic resin, 1.2 parts of stearic acid, 5 parts of white carbon black, 8 parts of carbon nanotubes, 0.5 parts of a coupling agent and 2 parts of an auxiliary agent in parts by weight, and dividing the carbon nanotubes and the coupling agent into two parts of equal weight; wherein the thermoplastic resin is obtained by mixing polyethylene, polypropylene and ethylene-vinyl acetate in a mass ratio of 2:2:1;

[0075] 2) setting the temperature of the open mill to 100° C., adding a thermoplastic resin and stearic acid to the open mill in sequence, and then adding a portion of carbon nanotubes and a coupling agent in five portions, and the mixing time is 25 minutes to prepare a masterbatch;

[0076] 3) The internal mixer was set to 130° C., the masterbatch was placed in the internal mixer, the additive was added, and then the other portion of carbon nanotubes and coupling agent were added in five portions, and finally white carbon black was added, and the internal mixing time was 35 minutes to obtain the internal mixing material;

[0077] 4) Set the open mill to 110°C, put the internally mixed material into the open mill for 10 minutes, cross-make triangle packages and roll three times each to obtain the open-mixed material;

[0078] 5) The roller temperatures of the first roller, the second roller and the third roller of the four-roll calender are set to 110°C, and the roller temperature of the fourth roller is set to 85°C; the roller gap between the first roller and the second roller is set to 0.5mm, the gap between the second roller and the third roller is set to 0.35mm, and the gap between the third roller and the fourth roller is set to 0.30mm; the milled material is placed on the rollers of the first roller and the second roller of the calender, the calendering speed is set to 1.4m / min, calendering is performed, and winding is performed at the end of the fourth roller to obtain the absorbing patch.

[0079] Comparative Example 1

[0080] Comparative Example 1 is substantially the same as Example 1, except that in step 1), the thermoplastic resin is only polyethylene.

[0081] During the calendering process, the milled material cannot be coated on the calender roller and cannot be formed into an absorbing patch.

[0082] Comparative Example 2

[0083] Comparative Example 2 is substantially the same as Example 1, except that in step 1), the thermoplastic resin is only polypropylene.

[0084] During the calendering process, the milled material cannot be coated on the calender roller and cannot be formed into an absorbing patch.

[0085] Comparative Example 3

[0086] Comparative Example 3 is substantially the same as Example 1, except that in step 1), the thermoplastic resin is only ethylene vinyl acetate.

[0087] During the calendering process, the milled material tends to adhere to the calender roller and is difficult to peel off, so it is impossible to form an absorbing patch.

[0088] Comparative Example 4

[0089] Comparative Example 4 is substantially the same as Example 1, except that in step 1), the thermoplastic resin is only a mixture of polyethylene and polypropylene.

[0090] During the calendering process, the milled material cannot be coated on the calender roller and cannot be formed into an absorbing patch.

[0091] Comparative Example 5

[0092] Comparative Example 5 is substantially the same as Example 1, except that in step 1), the thermoplastic resin is only a mixture of polyethylene and ethylene-vinyl acetate.

[0093] Comparative Example 6

[0094] Comparative Example 6 is substantially the same as Example 1, except that in step 1), the thermoplastic resin is only a mixture of polypropylene and ethylene-vinyl acetate.

[0095] Comparative Example 7

[0096] Comparative Example 7 is substantially the same as Example 1, except that: in step 1), 100 parts of thermoplastic resin, 1 part of stearic acid, 3 parts of white carbon black, 2 parts of carbon nanotubes, 0.3 parts of coupling agent and 1 part of auxiliary agent are weighed in parts by weight.

[0097] Comparative Example 8

[0098] Comparative Example 8 is substantially the same as Example 1, except that: in step 1), 100 parts of thermoplastic resin, 1 part of stearic acid, 3 parts of white carbon black, 12 parts of carbon nanotubes, 0.3 parts of coupling agent and 1 part of auxiliary agent are weighed in parts by weight.

[0099] Comparative Example 9

[0100] Comparative Example 9 is substantially the same as Example 1, except that in step 3), white carbon black is not added.

[0101] Comparative Example 10

[0102] Comparative Example 10 is substantially the same as Example 1, except that in step 4), the roller temperatures of the first roller, the second roller and the third roller are set to 120°C, and the roller temperature of the fourth roller is set to 95°C.

[0103] Since the roller temperature is high during the calendering process, the milled material is difficult to peel off from the fourth roller of the calender after calendering, and the absorbing patch cannot be formed.

[0104] Comparative Example 11

[0105] Comparative Example 11 is substantially the same as Example 1, except that in step 4), the roller temperatures of the first roller, the second roller and the third roller are set to 90°C, and the roller temperature of the fourth roller is 75°C.

[0106] Since the roller temperature is relatively low during the calendering process, the milled material is difficult to be covered by the roller during the calendering process, and is prone to rebound and other phenomena, making it impossible to form an absorbing patch.

[0107] Comparative Example 12

[0108] Comparative Example 12 is basically the same as Example 1, except that in step 4), the gap between the first roller and the second roller is set to 0.6 mm, the gap between the second roller and the third roller is set to 0.45 mm, and the gap between the third roller and the fourth roller is set to 0.35 mm.

[0109] Comparative Example 13

[0110] Comparative Example 13 is basically the same as Example 1, except that in step 4), the gap between the first roller and the second roller is set to 0.35 mm, the gap between the second roller and the third roller is set to 0.25 mm, and the gap between the third roller and the fourth roller is set to 0.2 mm.

[0111] Comparative Example 14

[0112] Comparative Example 14 is substantially the same as Example 1, except that in step 5), the calendering speed is 1 m / min.

[0113] As the sheet output speed is too slow, the milled material placed on the AB rollers of the calender has cooled down in the latter stage and is difficult to be wrapped on the rollers, so the absorbing patch is difficult to form.

[0114] Comparative Example 15

[0115] Comparative Example 15 is substantially the same as Example 1, except that in step 5), the calendering speed is 2 m / min.

[0116] Since the speed of producing the sheets is too fast, the temperature of the absorbing patches is high when they are produced, so they are easy to stick together and difficult to form.

[0117] Comparative Example 16

[0118] 1) Weighing 100 parts of a thermoplastic resin, 1 part of stearic acid, 3 parts of white carbon black, 6 parts of carbon nanotubes, 0.3 parts of a coupling agent and 1 part of an auxiliary agent in parts by weight; wherein the thermoplastic resin is obtained by mixing polyethylene, polypropylene and ethylene-vinyl acetate in a mass ratio of 2:2:1;

[0119] 2) setting the temperature of the open mill to 90° C., adding thermoplastic resin and stearic acid to the open mill in sequence, and then adding carbon nanotubes and coupling agent in multiple times, and the mixing time is 20 minutes to prepare a masterbatch;

[0120] 3) The internal mixer was set to 120° C. The masterbatch was placed in the internal mixer, the additives were added, and then white carbon black was added. The internal mixer was mixed for 30 minutes to obtain the internal mixer material.

[0121] 4) Set the open mill to 100° C., put the internally mixed material into the open mill for 6 minutes, cross-make triangle packages and roll them at least three times each to obtain the open-mixed material;

[0122] 5) The roller temperatures of the first roller, the second roller and the third roller of the four-roll calender are set to 100°C, and the roller temperature of the fourth roller is set to 80°C; the roller gap between the first roller and the second roller is set to 0.4mm, the gap between the second roller and the third roller is set to 0.31mm, and the gap between the third roller and the fourth roller is set to 0.28mm; the milled material is placed on the rollers of the first roller and the second roller of the calender, the calendering speed is set to 1.3m / min, calendering is performed, and winding is performed at the end of the fourth roller to obtain the absorbing patch.

[0123] The performance data of the absorbing patches of Examples 1-3 of the present invention and Comparative Examples 1-16 are shown in Table 1.

[0124] Table 1

[0125]

[0126] It should be noted that "—" in the table indicates that the absorbing patch is not formed and the performance test cannot be performed; it can be seen from the table that the absorbing patch prepared by the present invention has high thickness accuracy, light weight, high tensile strength, and excellent Ka-band absorbing performance; in Comparative Example 5, polypropylene is not added to the thermoplastic resin, and the tensile strength of the absorbing patch is significantly lower than that of the embodiment; in Comparative Example 6, polyethylene is not added to the thermoplastic resin, and the tensile strength of the absorbing patch is increased, but the thickness accuracy is poor and the Ka-band absorbing performance is also significantly deteriorated; in Comparative Example 7, white carbon black and carbon nanotubes are added to the thermoplastic resin. The mass ratio of white carbon black and carbon nanotubes is too large, and the tensile strength and Ka-band absorbing performance of the obtained absorbing patch are significantly reduced; in Comparative Example 8, the mass ratio of white carbon black and carbon nanotubes is too small, and the tensile strength of the obtained absorbing patch is increased, but the Ka-band absorbing performance is also significantly deteriorated; in Comparative Example 9, no white carbon black is added, and the tensile strength and Ka-band absorbing performance of the obtained absorbing patch are significantly reduced; It can be seen from Comparative Examples 12-13 that if the gap between the rollers of the calender is too large or too small, the thickness accuracy and Ka-band absorbing performance of the obtained absorbing patch will be significantly deteriorated.

[0127] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, a person skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A microwave absorbing patch, characterized in that: The raw materials for preparing the absorbing patch include the following components in parts by weight: 100 parts of thermoplastic resin, 1-1.2 parts of stearic acid, 3-5 parts of white carbon black, 6-8 parts of carbon nanotubes, 0.3-0.5 parts of coupling agent, and 1-2 parts of auxiliary agent; the thermoplastic resin is obtained by mixing polyethylene, polypropylene and ethylene-vinyl acetate; the mass ratio of polyethylene, polypropylene and ethylene-vinyl acetate in the thermoplastic resin is (35-45):(35-45):(15-25); The preparation method of the absorbing patch comprises: S1. performing a first refining of a mixture of a thermoplastic resin, stearic acid, carbon nanotubes and a coupling agent to obtain a masterbatch; S2. The mixture of the masterbatch, additives, carbon nanotubes, coupling agent and white carbon black is mixed to obtain a mixed material; S3. The refining material is subjected to a second refining to obtain a refining material; S4. The open-refined material is rolled and rolled to obtain the absorbing patch; The temperature of the first open refining is 90-100°C, and the time is 30-35 minutes; the temperature of the banburying is 120-130°C, and the time is 20-25 minutes; the temperature of the second open refining is 100-110°C, and the time is 6-10 minutes; The calendering is performed by a four-roll calender; the four-roll calender comprises a first roller, a second roller, a third roller and a fourth roller arranged in sequence from front to back; The roller temperature of the first roller is 100-110°C; the roller temperature of the second roller is 100-110°C; the roller temperature of the third roller is 100-110°C; the roller temperature of the fourth roller is 80-85°C; The gap between the first roller and the second roller is 0.4-0.5 mm; the gap between the second roller and the third roller is 0.31-0.35 mm; the gap between the third roller and the fourth roller is 0.28-0.30 mm; The sheet output speed of the calendering is 1.3-1.4 m / min.

2. The absorbing patch according to claim 1, characterized in that: The mass ratio of polyethylene, polypropylene and ethylene-vinyl acetate in the thermoplastic resin is 2:2:

1.

3. The absorbing patch according to claim 1, characterized in that: The coupling agent is a silane coupling agent; and / or The auxiliary agent is one or more of an antioxidant, an antibacterial agent, and an antioxidant.

4. The absorbing patch according to claim 3, characterized in that: The coupling agent is one or more of Si69, Si75, and KH550.

5. The absorbing patch according to claim 1, characterized in that: The thickness of the absorbing patch is 0.33-0.35 mm, and the thickness accuracy is ≤±0.01 mm; the surface density of the absorbing patch is ≤350 g / m 2 ; and / or The tensile strength of the absorbing patch is ≥6MPa.

Citation Information

Patent Citations

  • Process for producing optical film made of thermoplastic resin

    CN101801638A

  • Preparation method for synergetic reinforcing and toughening polypropylene composite material

    CN105398062A